Information systems strategic management : an integrated approach - Clarke, Steve , 1950- (New York : Routledge, 2007)
This volume provides a guide to the strategic management of information systems within business and the public sector. It considers the need to manage information systems as a mixture of technical and social entities, within a broader context.
1.Information systems strategic management : an integrated approach -- 2. Lessons from corporate strategy -- 3. Lessons from corporate strategy -- 4. Information systems strategy and system failure -- 5. Information systems applications and portfolio management -- 6. Competitive advantage from information systems -- 7. Structure, culture and change management in information systems -- 8. IS strategy and the Internet -- 9. Strategic implications of information security -- 10. Planning and formulating information systems strategy -- 11. Information systems strategic planning : a technical or social process?
Includes bibliographical references and index
Keywords: Management information systems; Management information systems -- Case studies; Strategic planning; Strategic planning -- Case studies